Implementation of production principles of islamic economics in Putra Mandiri Fish Business in Semarang City - Nur Burhanuddin; Anton Bawono (Institute of Computer Science (IOCS), 2022)
In an effort to improve the welfare of a country, good production is needed where it does not disrupt the sustainability of natural resources and maintain social ethics. Good production activities can be carried out through the implementation of principles of the Islamic economy, but not all Muslim producers have implemented the principle. The purpose of the study is to analyze the implementation of the principles of Islamic economics in the fish production company